Analisis Faktor Penyebab Stres Kerja Pada Pemandu Lalu Lintas Udara Di Airnav Bandar Udara Internasional Adi Soemarmo Solo - Asya Putri Setyadevi; Hodi (Jurnal Kajian dan Penelitian Umum, 2023)
Air Traffic Control (PLLU) is a profession that has a high level of stress because the workload of PLLU is very heavy which risks the lives of aircraft passengers and all flight crew. Stress is the effect of a high workload. This research is to find out what factors are considered to be a source of stress by PLLU officers and to find out how to deal with work stress on PLLU officers at Adi Soemarmo Solo International Airport. This research is a qualitative research. Data collection techniques used are observation, interviews and documentation. Observation of this study by direct observation of the Airnav unit at Adi Soemamro International Airport. interviews consisting of 3 informants namely Airnav PLLU officers, 1 Supervisor Officer and 1 Airnav HRD/HR officer. The results of this study can be concluded that the factors considered to be a source of work stress by PLLU officers at Adi Soemarmo Solo International Airport are boredom, stress, and burnout, both mentally and physically burdened. The physical load can be seen from the amount of physical activity, and the mental workload on PLLU Airnav officers at the Adi Soemamarm International Airport branch. Ways to deal with work stress on PLLU officers, namely by exercising regularly, eating nutritious food, getting enough rest and adopting a healthy lifestyle in their daily lives, leaders and subordinates respect each other, proper salary and wages, sufficient workload, effective communication and sufficient leave, rest and recreation rights for officers, as well as attention to conditions outside the work itself such as paying attention to the conditions of the employee's household..